Rehabilitation Effects of Traditional Chinese Medicine Hot Pressing on Female Patients with Stress Urinary Incontinence - HUANG Huirong; LIU Qinyu; YU Zhenling; WU Cuijuan; XUE Jialu; QIU Zhiqin; YU Mengxia (康复学报)
ObjectiveTo investigate the rehabilitation effects of traditional Chinese medicine hot pressing on female patients with stress urinary incontinence (SUI).MethodsA total of 80 patients with female SUI were selected and divided into experimental group and control group according to computer random grouping method, with 40 cases in each group. Finally, 77 patients completed the study with 2 cases dropped out in the experimental group and 1 case dropped out in the control group. The control group was treated with conventional rehabilitation and nursing, and the experimental group was given traditional Chinese medicine hot pressing additionally. Both groups were treated for 4 weeks. The leakage of urine (1-hour pad test) and Urogenital Distress Inventory (UDI-6) score before and after treatment and the Incontinence Quality of Life Questionnaire (I-QOL) scores before and after treatment and 1 month follow-up were evaluated.Results1) The urine leakage of 1-hour pad test in both groups after treatment was less than before treatment, and the difference was statistically significant (P<0.05). After treatment, the amount of urine leakage in the experimental group was less than that in the control group, and the difference was statistically significant (P<0.05). 2) After treatment, the irritation symptoms, stress symptoms, discomfort symptoms and the total scores of UDI-6 were found significantly lower in the experimental group than in the control group (P<0.05). These scores were significantly lower in both groups after treatment (P<0.05), except for the discomfort symptoms in the control group. 3) In the dimensions of limited behavior, psychological impact, social barriers and total scores of I-QOL, the intergroup, time and intergroup, and time interaction effects of the two groups were statistically significant (P<0.05). After treatment and at follow-up, the scores of overall I-QOL and limited behaviors, psychological impacts, social barriers were improved in both groups (P<0.05), and the experimental group improved more than the control group (P<0.05). At follow-up, the score of social barriers in the experimental group was higher than that after treatment (P<0.05), but there were no significant differences in the scores of overall I-QOL and other dimensions compared with those after treatment (P>0.05).ConclusionTraditional Chinese medicine hot pressing can improve the symptoms of urinary leakage in female patients with SUI and enhance the quality of life, which is better than conventional rehabilitation and nursing.